1988
DOI: 10.1021/bi00419a029
|View full text |Cite
|
Sign up to set email alerts
|

Rat kidney L-2-hydroxyacid oxidase. Structural and mechanistic comparison with flavocytochrome b2 from bakers' yeast

Abstract: Hydroxyacid oxidase from rat kidney is an FMN-dependent enzyme that catalyzes the oxidation of L-alpha-hydroxy acids as well as, more slowly, that of L-alpha-amino acids. We report here a modified purification method for the enzyme, which is found to possess one cofactor per subunit of Mr 39,000. Determination of its N-terminal sequence suggests the protein is homologous to spinach glycolate oxidase and baker's yeast lactate dehydrogenase. In the presence of a hydroxy acid and of bromopyruvate, under anaerobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 45 publications
0
25
1
Order By: Relevance
“…For rHAO p, the flat maxima are observed at 451 -453 nm and 355-357 nm. Urban et al (1988) had determined a molar absorption coefficient of 11 700 M-' cm-' at 452 nm for the enzyme purified from rat kidney. When this figure was used for calculating the protein concentration and the flavin content was separately determined by fluorimetry (see Materials and Methods), the two estimates fell within 6 % of each other for isozyme p, and within 2 % for a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For rHAO p, the flat maxima are observed at 451 -453 nm and 355-357 nm. Urban et al (1988) had determined a molar absorption coefficient of 11 700 M-' cm-' at 452 nm for the enzyme purified from rat kidney. When this figure was used for calculating the protein concentration and the flavin content was separately determined by fluorimetry (see Materials and Methods), the two estimates fell within 6 % of each other for isozyme p, and within 2 % for a.…”
Section: Resultsmentioning
confidence: 99%
“…To answer some of these questions, we started studying H A 0 as an oxidase prototype, insofar as it shows a number of interesting kinetic similarities with flavocytochrome b,, a dehydrogenase-electron transferase prototype (Lindqvist et al, 1991 ;Urban et al, 1988). We recently cloned and sequenced the cDNA encoding HA0 from rat kidney (Belmouden et al, 1993).…”
mentioning
confidence: 99%
“…Its absorbance at 280 nm was rather low and in fair agreement with Trp content, and its molecular mass (37 760 Da), as derived from Table II, was consistent with that obtained by SDS-polyacrylamide gel electrophoresis. Since a value of 169 kDa was obtained under nondenaturing conditions (not shown), it was concluded that chicken liver L-2-HAOX A is composed of 4 apparently identical subunits as all the enzymes of the A-type so far isolated from mammals [3,7] and plants [13,20].…”
Section: Some Molecular Propertiesmentioning
confidence: 96%
“…This was shown to originate from the existence of two isozymic forms of L-2-HAOX which were further isolated and partially characterized [3]. The rat liver L-2-HAOX (isozyme A) preferentially oxidized shortchain aliphatic 2-hydroxyacids with maximal activity towards glycolate [4,5], whereas the kidney enzyme (isozyme B) catalysed the oxidation of long-chain aliphatic or aromatic 2-hydroxyacids at the highest rates [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation